Thermal Runaway of Li-Ion Cells: How Internal Dynamics, Mass Ejection, and Heat Vary with Cell Geometry and Abuse Type. Issue 2 (1st February 2022) - Sharp, Matthew; Darst, John Jacob; Hughes, Peter; Billman, Julia; Pham, Martin; Petrushenko, David; Heenan, Thomas M. M.; Jervis, Rhodri; Owen, Rhodri; Patel, Drasti; Wenjia, Du; Michael, Harry; et al.
Abstract : Thermal runaway of lithium-ion batteries can involve various types of failure mechanisms each with their own unique characteristics. Using fractional thermal runaway calorimetry and high-speed radiography, the response of three different geometries of cylindrical cell (18650, 21700, and D-cell) to different abuse mechanisms (thermal, internal short circuiting, and nail penetration) are quantified and statistically examined. Correlations between the geometry of cells and their thermal behavior are identified, such as increasing heat output per amp-hour (kJ Ah −1 ) of cells with increasing cell diameter during nail penetration. High-speed radiography reveals that the rate of thermal runaway propagation within cells is generally highest for nail penetration where there is a relative increase in rate of propagation with increasing diameter, compared to thermal or internal short-circuiting abuse. For a given cell model tested under the same conditions, a distribution of heat output is observed with a trend of increasing heat output with increased mass ejection. Finally, internal temperature measurements using thermocouples embedded in the penetrating nail are shown to be unreliable thus demonstrating the need for care when using thermocouples where the temperature is rapidly changing. All data used in this manuscript are open access through the NREL and NASA Battery Failure Databank.